2014
DOI: 10.2343/geochemj.2.0320
|View full text |Cite
|
Sign up to set email alerts
|

Regional mantle heterogeneity regulates melt production along the Réunion hotspot-influenced Central Indian Ridge

Abstract: production by geochemically distinct magmas is a typical phenomenon along hotspot-influenced mid-ocean ridge (e.g., Ito et al., 2003; Schilling et al., 1982). The style of ridge-hotspot interaction are classifiable into three categories on the basis of the ridge-hotspot distance (Dyment et al., 2007). Along ridges directly over or in proximity to a hotspot, systematic geochemical variations can be determined corresponding to crustal volume, such as those seen on the Mid-Atlantic Ridge to near Iceland (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 64 publications
1
9
1
Order By: Relevance
“…In addition, our new samples from segments 5 and 6 present uniform Ce/Pb (∼17–21) and Nb/U (∼35–41) (Figure 3). The variations in these trace element ratios are of the same order of magnitude as previously reported for samples from segments 5 and 6 (and those encountered along the Rodrigues segment, south of MCFZ (Füri et al., 2011; Kim et al., 2017; Machida et al., 2014; Murton et al., 2005; Nauret et al., 2006). Overall, segment 6 shows higher variability in Ce/Pb with ratios from ∼15 to 28 compared to segment 5 (Ce/Pb = 17 to 23).…”
Section: Resultssupporting
confidence: 81%
“…In addition, our new samples from segments 5 and 6 present uniform Ce/Pb (∼17–21) and Nb/U (∼35–41) (Figure 3). The variations in these trace element ratios are of the same order of magnitude as previously reported for samples from segments 5 and 6 (and those encountered along the Rodrigues segment, south of MCFZ (Füri et al., 2011; Kim et al., 2017; Machida et al., 2014; Murton et al., 2005; Nauret et al., 2006). Overall, segment 6 shows higher variability in Ce/Pb with ratios from ∼15 to 28 compared to segment 5 (Ce/Pb = 17 to 23).…”
Section: Resultssupporting
confidence: 81%
“…The axial valley seafloor of segments 15 and 16 has little terrigenous sediment. It has been revealed that potassium and helium-3 are enriched in the basalts collected from the spreading axes and off axes of these segments, although the cause of such petrological characteristics is under debate (Murton et al 2005;Nauret et al 2006;F€ uri et al 2011;Machida et al 2014).…”
Section: Observation Geological Backgroundmentioning
confidence: 99%
“…() have interpreted this discordance as the result of interactions between the Réunion hotspot and the nearby Central Indian Ridge. Rodrigues is located in a tectonically undisturbed area some 900 km north‐east of the Rodrigues Triple Junction (Machida et al ., ), and the older estimate is actually the age of the tectonic evolution of the Rodrigues Triple Junction (Mendel et al ., ). Other SWIO volcanic islands include the Comoros, and Aldabra, an 8 m high coral atoll of Pleistocene age.…”
Section: Geologymentioning
confidence: 99%